Cosmetic Potential of Haberlea rhodopensis Extracts and Extracellular Vesicles in Human Fibroblast Cells - Milena Georgieva; Bela Vasileva; Penyo Ivanov; Kamelia Hristova-Panusheva; Tsvetelina Paunova-Krasteva; Ivan Lesov; Zlatina Gospodinova; Natalia Krasteva; George Miloshev; Vasil Georgiev (Cosmetics)
Skin ageing is a complex biological process influenced by cellular senescence, oxidative stress, and extracellular matrix degradation. Emerging evidence suggests that plant-derived bioactive compounds and extracellular vesicles (EVs) play a crucial role in modulating cellular homeostasis, promoting tissue regeneration, and counteracting age-related morphological and functional changes. This study investigates the impact of Haberlea rhodopensis in vitro culture extracts, native and enriched with EVs, on key cellular processes, including morphology, mitochondrial dynamics, lysosomal activity, gene expression, and genotoxicity in human dermal fibroblasts. The extracellular vesicles were identified in terms of shape, size, and morphology using dynamic light scattering, negative staining and observation under a transmission electron microscope. A comprehensive in vitro analysis was conducted utilizing light microscopy to assess cellular morphology and lysosomal mass, fluorescence microscopy for actin cytoskeletal organization, mitochondrial integrity, and nuclear morphology, and gene expression profiling for markers associated with collagen synthesis (COL1A1, COL3A1), senescence (CDKN1A), and oxidative stress response (NFE2L2). Additionally, cell cycle progression was evaluated, and genotoxicity was assessed using the neutral comet assay. Haberlea rhodopensis in vitro culture extracts and EVs were found to preserve fibroblast morphology, enhance mitochondrial mass, and upregulate collagen-related gene expression. These effects were concentration-dependent. The extracts exhibited biocompatibility with minimal genotoxic effects, indicating their potential as safe bioactive agents for skin rejuvenation. The findings suggest that Haberlea rhodopensis in vitro culture extracts and their enrichment with extracellular vesicles hold promise for cosmetic and dermatological applications, particularly in enhancing collagen production, preserving cellular integrity, and mitigating age-related alterations in skin fibroblasts. Further studies are warranted to elucidate the underlying molecular mechanisms and optimize formulation strategies for clinical translation.